Determination of A Firm Value with CSR as a Moderation Variable - Dinda Spanyolia Agassi; Achmad Saiful Ulum Ulum (Jurnal Manajemen dan Keuangan, 2023)
The study aims to test the effect of profitability, leverage, and corporate size on a Firm Value with CSR as a moderation variable. Based on research methods, this research is classified as pure research. The method of data collection used in this study is to use the method of documentation through the company's financial statements published through the official website of the Indonesia Stock Exchange (IDX) which is www.idx.co.id. The population in this study used companies listed on the Indonesia Stock Exchange for the period 2015-2020. The sample used is a manufacturing company listed on the Indonesia stock exchange for the period 2015-2020. The sampling method uses purposive sampling with a sample of 24 companies that fit the criteria. Data analysis techniques use multiple linear regression analysis and multiple regression analysis, using spss software application version 25. The results showed that simultaneously profitability, leverage, and the size of the company had a significant effect on the Firm Value. Partially profitability and laverage have a significant positive effect on the Firm Value. But the size of the company has no effect on the Firm Value. CSR variables are able to moderate the influence of profitability and the influence of leverage on the Firm Value. But at the size of the company, corporate social responsibility is not able to moderate the influence of the size of the company on the Firm Value